Visualization- and analytics-supported video-based professional development for promoting mathematics classroom discourse. (April 2022) - Chen, Gaowei; Chan, Carol K.K.
Abstract: Although classroom discourse that positions students as active participants benefits both their learning and cognitive development, teachers often find it challenging to implement dialogic instructions in the classroom. This study reports on a video-based teacher professional development (PD) program that leverages visualizations and analytics in supporting teacher change in whole-class dialogue in mathematics classrooms. Both experimental and comparison teachers ( n  = 24 and 22, respectively) were provided with information on dialogic instructions, and experimental teachers used the Classroom Discourse Analyzer to reflect on videos of their lessons and their peers' lessons in a year-long PD program. The intervention teachers significantly moved toward less dominant classroom talk—they reduced the number of words spoken per lesson, and their students significantly increased the number of words per turn in whole-class discussions, relative to the comparison teachers. Furthermore, analysis of the classroom discourse shows qualitative changes in the intervention teachers' discourse. PD workshop and teacher self-reflection data are analyzed to examine how visualizations and analytics in the PD program may serve as a cross-boundary object to support peer collaboration in reflective practice, and to increase teachers' awareness of their teaching development.